2021
DOI: 10.1007/s00345-021-03839-7
|View full text |Cite
|
Sign up to set email alerts
|

Occult lymph node metastases in patients without residual muscle-invasive bladder cancer at radical cystectomy with or without neoadjuvant chemotherapy: a nationwide study of 5417 patients

Abstract: Purpose Little is known about the prevalence of occult lymph node metastases (LNM) in muscle-invasive bladder cancer (MIBC) patients with pathological downstaging of the primary tumor. We aimed to estimate the prevalence of occult LNM in patients without residual MIBC at radical cystectomy (RC) with or without neoadjuvant chemotherapy (NAC) or neoadjuvant radiotherapy (NAR), and to assess overall survival (OS). Methods Patients with cT2-T4aN0M0 urothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Another study reported that 5‐year overall survival of patients with residual cancer (ypT2‐4 or ypN+) after NAC was 21%, whereas that of cases with pCR was 82% 12 . Occult LNM after RC also showed a poor prognosis 13,14 . In the PURE‐01 study of neoadjuvant pembrolizumab, all MIBC patients enrolled in the study underwent RC, and 42% of patients achieved pCR 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that 5‐year overall survival of patients with residual cancer (ypT2‐4 or ypN+) after NAC was 21%, whereas that of cases with pCR was 82% 12 . Occult LNM after RC also showed a poor prognosis 13,14 . In the PURE‐01 study of neoadjuvant pembrolizumab, all MIBC patients enrolled in the study underwent RC, and 42% of patients achieved pCR 9 .…”
Section: Discussionmentioning
confidence: 99%
“… 12 Occult LNM after RC also showed a poor prognosis. 13 , 14 In the PURE‐01 study of neoadjuvant pembrolizumab, all MIBC patients enrolled in the study underwent RC, and 42% of patients achieved pCR. 9 Considering the poor prognosis of ypN+ cases after NAC and RC, systemic immunotherapy with a view to converting RC may increase the possibility of cure.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The rate of occult lymph node metastases is high (4%) and important to consider when counselling patients, because it directly impacts the survival of patients. 23 Apart from initial tumor stage other local individual patient findings may offer insights on potential outcomes of pT0. We present a comprehensive and contemporary analysis of those findings.…”
Section: Dovepressmentioning
confidence: 99%
“…Currently, there is an ongoing randomized control trial comparing a standard pelvic lymphadenectomy to an extended one at the time of radical cystectomy that will help clarify this [11]. However, despite the use of pelvic lymphadenectomy at the time of radical cystectomy, patients with nodal metastases have characteristically diminished overall survival even within the setting of no residual muscle invasive disease on final pathology at the time of radical cystectomy [6 ▪ ,12]. One study showed a median survival of 3.5 years in patients without residual primary tumor but residual nodal involvement at the time of cystectomy compared with 14.1 years in T0N0 bladder cancer [12].…”
Section: Radical Cystectomy and Pelvic Lymph Node Dissectionmentioning
confidence: 99%
“…However, despite the use of pelvic lymphadenectomy at the time of radical cystectomy, patients with nodal metastases have characteristically diminished overall survival even within the setting of no residual muscle invasive disease on final pathology at the time of radical cystectomy [6 ▪ ,12]. One study showed a median survival of 3.5 years in patients without residual primary tumor but residual nodal involvement at the time of cystectomy compared with 14.1 years in T0N0 bladder cancer [12]. Similarly, a study investigating survival outcomes in patients with clinically bulky nodal involvement showed reduced recurrence-free survival in node-positive patients.…”
Section: Radical Cystectomy and Pelvic Lymph Node Dissectionmentioning
confidence: 99%